Los valores como base cognitiva del autoritarismo y la dominancia - Zubieta, Elena M. (2022)
Sexism, xenophobia, or homophobia are based on values and beliefs about inequality between groups. To analyze the relationship between Right Wing Authoritarianism (RWA) and Social Dominance Orientation (SDO) with Values (Schwartz, 1992), an explanatory, non-experimental cross-sectional study was conducted based on an intentional sample composed by 407 university students (58.5% women; mean age 23.69 years). The findings ratify the RWA and SDO as conservative constructs structured in terms of power and in values opposed to non-aggressive intergroup relations, ratifying a general disposition to prejudice. Also, differential configurations showed up supporting the idea of the Dual Processing Model about the multidimensional nature of prejudice (Duckitt & Sibley, 2010).